(untitled) (Global Journal of Science Frontier Research, 2023)
Preventingenvironmental pollution is the primary goal of obtaining natural dyes from available natural sources The alkaline extraction process is used to extract dye from Tageteserecta leaves In 100 cotton and 60 40 CVC 60 cotton and 40 polyester single jersey weft knitted fabrics three different mordants CuSO4 FeSO4 and K2Cr2O7 are applied simultaneously At 100 C as well as at room temperature the dye fixing is done Various shades of yellow brown and light green were producedwhen the dye was treated with a mordant Comparing the dye fixed at 100 C to the dye fixed at room temperature the dye at 100 C displayed dark colors and good fastness qualities Tageteserecta dye extract demonstrated significant antibacterial action against gram-positive bacteria S aureus and FTIR was used to identify chemical components and functional groups